2020
DOI: 10.1186/s41747-020-00170-5
|View full text |Cite
|
Sign up to set email alerts
|

DBT-galactography: a promising tool for improving the diagnostic workup of nipple discharge

Abstract: Background: Our aim was to compare the diagnostic performance of digital breast tomosynthesis (DBT)galactography with that of full-field digital (FFD)-galactography for detecting intraductal breast lesions using an intra-individual design. Methods: Forty-nine consecutive patients with spontaneous, unilateral, single-pore nipple discharge and inconclusive FFD mammography and ultrasonography underwent galactography with a "COMBO" technique combining FFD-and DBT-galactography acquisitions. Examinations were indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In 49 patients with pathological nipple discharge, surgical pathological confirmation found that the DBT-galactography had higher sensitivity, specificity, PPV, and NPV than FFDM-galactography. This is consistent with the findings of Moschetta et al [18] that DBT-galactography is more sensitive, and that the application of DBT-galactography in catheter increases the confidence of diagnosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In 49 patients with pathological nipple discharge, surgical pathological confirmation found that the DBT-galactography had higher sensitivity, specificity, PPV, and NPV than FFDM-galactography. This is consistent with the findings of Moschetta et al [18] that DBT-galactography is more sensitive, and that the application of DBT-galactography in catheter increases the confidence of diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…In recent studies, Jong Yoon Lee et al [17] applied DBT in galactography and retrospectively analyzed the application of DBT and SM 2D in catheterization in 35 cases. Marco Moschetta et al [18] compared the diagnostic performance of DBT-galactography with that of FFD-galactography [18].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, mammary ductoscopy is a technology that allows for the direct visualization and biopsy examination of the mammary ductal abnormalities [26,27]. Furthermore, recent studies [28,29] have reported that digital breast tomosynthesis-GL may become an important diagnostic step for managing PND.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 There are several studies evaluating digital breast tomosynthesis (DBT) galactography (ductography) for nipple discharge workup, comparing it with traditional 2D digital mammography ductography, but there were no reports published on the diagnostic performance of DBT in the evaluation of nipple discharge. 8,9 The aim of this study is to assess the value of DBT in evaluating patients with nipple discharge and to compare it with MMG, US, and MRI.…”
Section: Introductionmentioning
confidence: 99%